Forest wildflowers bloom earlier as Europe warms: lessons from herbaria and spatial modelling. Issue 1 (28th April 2022) - Willems, Franziska M.; Scheepens, J. F.; Bossdorf, Oliver
Summary: Today plants often flower earlier due to climate warming. Herbarium specimens are excellent witnesses of such long‐term changes. However, the magnitude of phenological shifts may vary geographically, and the data are often clustered. Therefore, large‐scale analyses of herbarium data are prone to pseudoreplication and geographical biases. We studied over 6000 herbarium specimens of 20 spring‐flowering forest understory herbs from Europe to understand how their phenology had changed during the last century. We estimated phenology trends with or without taking spatial autocorrelation into account. On average plants now flowered over 6 d earlier than at the beginning of the last century. These changes were strongly associated with warmer spring temperatures. Flowering time advanced 3.6 d per 1°C warming. Spatial modelling showed that, in some parts of Europe, plants flowered earlier or later than expected. Without accounting for this, the estimates of phenological shifts were biased and model fits were poor. Our study indicates that forest wildflowers in Europe strongly advanced their phenology in response to climate change. However, these phenological shifts differ geographically. This shows that it is crucial to combine the analysis of herbarium data with spatial modelling when testing for long‐term phenology trends across large spatial scales.